3D Bioprinting for fabrication of tissue models of COVID-19 infection. Issue 3 (10th August 2021) - Kabir, Anisha; Datta, Pallab; Oh, Julia; Williams, Adam; Ozbolat, Veli; Unutmaz, Derya; T. Ozbolat, Ibrahim
Abstract: Over the last few decades, the world has witnessed multiple viral pandemics, the current severe acute respiratory syndrome-related coronavirus 2 (SARS-CoV-2) pandemic being the worst and most devastating one, claiming millions of lives worldwide. Physicians, scientists, and engineers worldwide have joined hands in dealing with the current situation at an impressive speed and efficiency. One of the major reasons for the delay in response is our limited understanding of the mechanism of action and individual effects of the virus on different tissues and organs. Advances in 3D bioprinting have opened up a whole new area to explore and utilize the technology in fabricating models of these tissues and organs, recapitulating in vivo environment. These biomimetic models can not only be utilized in learning the infection pathways and drug toxicology studies but also minimize the need for animal models and shorten the time span for human clinical trials. The current review aims to integrate the existing developments in bioprinting techniques, and their implementation to develop tissue models, which has implications for SARS-CoV-2 infection. Future translation of these models has also been discussed with respect to the pandemic.